2004
DOI: 10.4269/ajtmh.2004.70.532
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous Peritonitis in Different Dialysis Patients in Southern Taiwan

Abstract: Eleven cases of tuberculous peritonitis (TBP) in hemodialysis (HD) and continuous ambulatory peritoneal dialysis (CAPD) patients at the Kaohsiung Veterans General Hospital in Kaohsiung, Taiwan between 1991 and 2000 were studied retrospectively (six cases in the HD group and five cases in the CAPD group) The diagnosis of TBP was established by either positive ascite tuberculosis (TB) culture or biopsy-proven chronic granulomatous inflammation. Fever and abdominal pain were the most common symptoms, while leukoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…Notably, treatment delay has been proven to be the most important predictive factor of mortality from TB peritonitis [5,16]. Recently, a retrospective study from Taiwan revealed that laparoscopic biopsy was safe and could provide a prompt diagnosis of TB peritonitis, resulting in low morbidity and mortality among patients undergoing dialysis [17]. In general, complications of laparoscopy are uncommon, and the reported mortality is !0.1% [18].…”
Section: Discussionmentioning
confidence: 98%
“…Notably, treatment delay has been proven to be the most important predictive factor of mortality from TB peritonitis [5,16]. Recently, a retrospective study from Taiwan revealed that laparoscopic biopsy was safe and could provide a prompt diagnosis of TB peritonitis, resulting in low morbidity and mortality among patients undergoing dialysis [17]. In general, complications of laparoscopy are uncommon, and the reported mortality is !0.1% [18].…”
Section: Discussionmentioning
confidence: 98%
“…However, hypercalcemia is frequently reported to occur in tuberculosis patients with chronic kidney disease, including patients receiving peritoneal dialysis or hemodialysis (124126). Tuberculosis-associated hypercalcemia has even been observed in anephric patients (119, 120, 122).…”
Section: Hypercalcemiamentioning
confidence: 99%
“…However, hypercalcemia is frequently reported to occur in tuberculosis patients with chronic kidney disease, including patients receiving peritoneal dialysis or hemodialysis (124)(125)(126). Tuberculosis-associated hypercalcemia has even been observed in anephric patients (119,120,122).…”
Section: Hypercalcemiamentioning
confidence: 99%